2007
DOI: 10.1007/s11524-007-9213-3
|View full text |Cite
|
Sign up to set email alerts
|

Community Characteristics Associated with HIV Risk among Injection Drug Users in the San Francisco Bay Area: A Multilevel Analysis

Abstract: Community characteristics have been associated with racial and ethnic health disparities for a wide range of ailments and conditions. Previous research has found that rates of AIDS cases among injection drug users (IDUs) vary by community characteristics. However, few studies have examined whether community characteristics are associated with HIV risk behaviors among IDUs. To address this gap in the literature, we examined the associations between census-tract-level community characteristics and injection-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 46 publications
2
38
2
1
Order By: Relevance
“…While it is not unexpected that residing in areas with high concentrations of low income households would be associated with HRIB (Bluthenthal et al, 2007;Buchanan et al, 2003;Galea et al, 2003), we also found that higher neighbourhood educational attainment was associated with greater odds of HRIB, accounting for individual characteristics. One plausible explanation for this discordant latter finding is a possible tension between inner-city IDUs and university educated close neighbours which could adversely shape IDUs' behaviours, thus counteracting any potential advantages associated with high education concentration in a neighbourhood.…”
Section: Figure 1 Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…While it is not unexpected that residing in areas with high concentrations of low income households would be associated with HRIB (Bluthenthal et al, 2007;Buchanan et al, 2003;Galea et al, 2003), we also found that higher neighbourhood educational attainment was associated with greater odds of HRIB, accounting for individual characteristics. One plausible explanation for this discordant latter finding is a possible tension between inner-city IDUs and university educated close neighbours which could adversely shape IDUs' behaviours, thus counteracting any potential advantages associated with high education concentration in a neighbourhood.…”
Section: Figure 1 Discussioncontrasting
confidence: 45%
“…In American cities, individual injection drug use patterns were found to be associated with living in an economically disadvantaged neighbourhood and/or a low educational attainment neighbourhood (Bluthenthal et al, 2007;Buchanan et al, 2003;Fuller et al, 2005;Galea et al, 2003). Other research indicates that neighbourhood income is more strongly related to the health of low income residents than that of the more advantaged (Boardman et al, 2001;Stafford & Marmot, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Past research has concluded that local racial/ethnic composition is related to the odds that an individual will engage in RSS. 52 We analyzed US census data to calculate the percent of district residents who were non-Hispanic White during each year of the study period.…”
Section: District-level Measuresmentioning
confidence: 99%
“…Many factors lead to an increasing drug use. Studies have found that prevalent drug use is related to demographic and socioeconomic strategies [11]. For instance, they showed more precise correlations between community characteristics and HIV infection among individuals with injecting drug use than their individual behaviors.…”
Section: Behavioral Interventionsmentioning
confidence: 99%